Observations of bay-breeze and ozone events over a marine site during the OWLETS-2 campaign. (15th October 2021) - Caicedo, Vanessa; Delgado, Ruben; Luke, Winston T.; Ren, Xinrong; Kelley, Paul; Stratton, Phillip R.; Dickerson, Russell R.; Berkoff, Timothy A.; Gronoff, Guillaume
Abstract: Land-sea recirculation such as bay and sea-breezes are important local circulations that facilitate pollution events. Measurements over a marine site in the Chesapeake Bay revealed the evolution of two bay-breeze events and associated ozone vertical structure. The horizontal and vertical structure of the bay-breeze was detailed using scanning Doppler wind lidar measurements and a ground-based ozone lidar was used to characterize the vertical distribution of ozone. The two bay-breeze events on 29–30 June 2018 observed during the Ozone Water-Land Environmental Transition Study Phase 2 (OWLETS-2) campaign showed distinct differences in the horizontal and vertical evolution of wind as well as the accompanying vertical structure of ozone. The analysis of the wind circulation showed that the intensity of the offshore flow plays an important role in the initiation time, development, and strength of the bay-breeze on both days. Results showed increased surface ozone concentrations during times of relatively low or decreasing bay-breeze height and weak upwards vertical motion. Upwards vertical motions were significantly enhanced on 30 June 2018 and presented with a decrease in surface ozone concentrations, yet enhanced ozone values were lofted above the surface near the lofted offshore flow. This study shows that both the vertical structure and evolution of pollutants can be impacted by the bay-breeze events through dilution and transport. Highlights: Two bay-breeze events distinctively different in the horizontal and vertical evolution of wind and ozone vertical structure. Intensity of the offshore flow is important in the initiation time, development, and strength of the bay-breeze. Increased surface ozone concentrations during times of relatively low bay-breeze height and weak upwards vertical motion. Enhanced ozone values were lofted above the surface near the lofted offshore flow.